Analisis Faktor-Faktor yang Mempengaruhi Nilai Informasi Pelaporan Keuangan Pemerintah Daerah (Studi Pada Satuan Kerja Perangkat Daerah di Kabupaten Sampang) - Dwi Anita Indrawati; Mohamad Djasuli (LPPM Universitas Trunojoyo Madura, 2016)
This research was aimed to figure out any factors having influence related to local government financial report information value. Those investigated factors were human resources quality, IT utilization, local financial control and supervisory system. The data collection were conducted by giving questionnaires to respondents working as civil servants whose duty are related to financial management/accounting function at SKPD consisting head or staff of sub PPK-SKPD and treasurer of SKPD Sampang Regency. The collected data were then analyzed by using SPSS 16.00. The test result showed that the quality of human resources contributed significantly positive to local government financial report information value. In addition, IT utilization also gave significantly positive contribution to the value mentioned previously. Internal control system, another factor, influenced significantly positive to the same value while local financial supervision, the last factor in this research, also significantly incited to the value being discussed in this research.